Pengembangan Media Edukatif Berbasis Video Tiktok Pada Materi Statistika (Mean, Median, Modus) Untuk Siswa MTs - Safrina, Khusnul; Azhari, Budi; Putri, Nabilla Radhliya (Jurnal PEKA (Pendidikan Matematika), 2026)
This study aims to develop TikTok video–based educational media for teaching statistics to junior high school (MTs) students and to describe the development process. The study employs the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The subjects of the study include 20 students from class VIII MTsN Banda Aceh and one mathematics teacher at MTsN 4 Banda Aceh. The results show that the development process of the TikTok video-based educational media product follows the 4D stages. Furthermore, the findings indicate that the validity level of the product, in terms of content, falls into the valid category with an average Aiken’s (V) score of 0.744, while in terms of media aspects it is categorized as very valid with a score of 0.904. The practicality level of the product was categorized as practical, with a teacher response percentage of 75%. Meanwhile, students’ responses reached 81%, which was categorized as practical.